2010
DOI: 10.1002/ejic.201000487
|View full text |Cite
|
Sign up to set email alerts
|

From Salicylaldehyde to Chiral Salen Sulfonates – Syntheses, Structures and Properties of New Transition Metal Complexes Derived from Sulfonato Salen Ligands

Abstract: Coordination complexes derived from chiral and nonchiral sulfonato salen ligands {(SalenSO3)Na2: N,N′‐bis(5‐sulfonatosalicylidene)‐1,2‐diaminoethane disodium salt, [(R,R) and (S,S)‐CySalenSO3]NaK: (R,R) and (S,S)‐N,N′‐bis(5‐sulfonatosalicylidene)‐1,2‐diaminocyclohexane sodium–potassium salt} have been synthesized. The crystal structures of the chiral and nonchiral NiII complexes [Ni(SalenSO3)]Na2 (1) and [Ni((R,R)CySalenSO3)]NaK (2) were solved. The other chiral and nonchiral sulfonato salen complexes, [Cu(Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…[85,86] This difference is merely a result of the higher spin density along the C-C bond of the carboxylates than along the C-S bond of the sulfonates within the anchoring moieties. These complexes were successfully inserted and grafted into copper and cobalt LSHs.…”
Section: Discussionmentioning
confidence: 99%
“…[85,86] This difference is merely a result of the higher spin density along the C-C bond of the carboxylates than along the C-S bond of the sulfonates within the anchoring moieties. These complexes were successfully inserted and grafted into copper and cobalt LSHs.…”
Section: Discussionmentioning
confidence: 99%
“…[142,143] Brought to you by | Stockholms Universitet Authenticated Download Date | 8/15/15 9:13 PM involving different diamine bridges. [140,144,145] The insertion of such complexes generates specific difficulties due to their possible hydrolysis during the exchange reaction. [144] This difficulty has been overcome by working from (Figure 21).…”
Section: Hybrid Materials Including Photoactive Molecules or Complexementioning
confidence: 99%
“…[140,144,145] The insertion of such complexes generates specific difficulties due to their possible hydrolysis during the exchange reaction. [144] This difficulty has been overcome by working from (Figure 21). The cobalt compounds, noted MPcTS 0 @Co, have a ferrimagnetic behavior ( Figure 22) with Brought to you by | Stockholms Universitet Authenticated Download Date | 8/15/15 9:13 PM ordering temperatures of 5.8, 6.8 and 7.8 K for the compounds functionalized by the Co, Ni and Cu phthalocyanine, respectively.…”
Section: Hybrid Materials Including Photoactive Molecules or Complexementioning
confidence: 99%
“…[4] Zhou and coworkers reported that water-soluble Cu(salphen)s [salphen = N,NЈ-bis(salicylidene)imine-1,2-phenylenediamine] in the presence of a suitable base are excellent catalysts for converting various combinations of aldehydes, malononitrile and indoles into the respective 3-component reaction (3-CR) products (Scheme 1) and provide high yields by using water as the 4694 benzylidene malononitrile species. [7] This stability issue therefore raises the question as to whether or not water is truly the best solvent for this 3-CR process since the organic products needed to be isolated and purified by using organic solvents. The results led to a mechanistic proposal in which the benzylidene malononitrile intermediate plays a central role; it is one of the major species that is formed in most of the catalytic reactions studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we envisioned that the use of Zn II ‐ rather than Cu II ‐salphen complexes would be beneficial for effective synthesis of the 3‐substituted indoles. It is worth noting that recent work has shown that Cu‐ and Zn(salen)s have a tendency to decompose under aqueous conditions to provide access to “half‐salen” type intermediates 7. This stability issue therefore raises the question as to whether or not water is truly the best solvent for this 3‐CR process since the organic products needed to be isolated and purified by using organic solvents.…”
Section: Introductionmentioning
confidence: 99%